Green School Management at SMP Negeri 8 Pemalang, Pemalang District, Pemalang Regency - Teguh Gunarso; Endang Wuryandini; Muhtarom Muhtarom (Journal of Educational Sciences, 2026)
This study aims to describe the management of the green school at SMP Negeri 8 Pemalang. The research method used in this study is descriptive qualitative research. The research subjects include the principal, teachers, students, school janitors, school committee members, parents, and related partners. Data collection techniques involve interviews, observations, and documentation. Data analysis was conducted using the interactive model of Miles and Huberman. The validity using triangulation techniques and confirmability tests. The results show that the management of the green school includes environmentally oriented school policies, an environment-based curriculum, participatory activities, and the management of environmentally friendly supporting facilities and infrastructure. This is evidenced by the following activities: (1) green school planning is carried out by incorporating aspects of environmental education and involving the surrounding community in providing input and suggestions; (2) organizing is conducted through the formation of a coordinating team according to work programs and respective roles and functions; (3) implementation is realized through various policies and activity programs, environmental-based learning, increased participation of school members, and adequate facilities and infrastructure supporting environmental education; (4) controlling is carried out through regular evaluation and monitoring activities in the form of written regulations, verbal warnings, appeals, guidance, and awards.